Influence of salicylic acid on protein content and catalase activity in relation to systemic acquired resistance in cowpea against root rot - PRANAB KUMAR MANDAL and PRADEEP SAXENA, AMARESH CHANDRA, ANJALI ANAND (Indian Phytopathology, 2002)
Salicylic acid treatment as foliar spray caused a reduction in the root rot disease caused by Rhizoctonia so/ani to control as revealed by disease progress curve. Total soluble proteins and catalase activity in leaves were measured in seven genotypes of cowpea differing in their reaction to the disease sprayed with 0.02% salicylic acid. Soluble proteins declined in response to salicylic acid treatment in all genotypes except UPC 4200. Though maximum decline in catalase activity was observed initially in IGFRI 450, a significant drop in it was noticed in UPC 4200 until four days after treatment.